MALIK BENNABI DAN STRATEGI PEMBANGUNAN PERADABAN ALTERNATIF BAGI DUNIA KETIGA - Nurhakim, Moh. (Journal of Al-Tamaddun, 2008)
Malik Bennabi observes that contemporary challenge for the Muslims is due to the civilizational problem. The main causes are lacking of idea among Muslims from one hand and colonialism from other nations from the other hand. This article will focus on Bennabi?s efforts in reformating Islamic Civilization's structure which concentrates on the rise of human cultural aspect. He recommends for carrying some ?Cultural Project? or adopting an ?alternative civilizational strategy? especially for the third world.